Neoplasia of the Nictitating Membrane in A Domestic Short- Haired Cat based on Cytology of Fine Needle Aspiration - Fatimah Alaydrus; Lita Rakhma Yustinasari; Juliano Mwenda Ntoruru (Indian Journal of Forensic Medicine & Toxicology, 2021)
A 3-year-oldmaledomestic short-hairedcat was presented with the complain ofa dark red mass of thenictitating membrane of the right eyecovered most of the cornea, mucopurulent eye secret, lost appetite,medium dehydration, and cough. Physical examination was performed and showedhigh temperature (38,6°C).Ultrasonographic examination was not performed due to tool limitations. Cytologyof fine-needle aspirationmasses suggested an ophthalmic neoplasm with the characteristic of neutrophils infiltration, multinecluatedgiant cells, and cells having glanular cytoplasm.Enucleation bulbi was performed subsequentlyto exenterationthe eye and the contents of the orbit.